ANALISIS POLA PEMASARAN DAN PROFITABILITAS IKAN LELE (Clarias sp) DI KOTA BATURAJA KABUPATEN OGAN KOMERING ULU (JASEP, 2016)
Profitability Analysis and Pattern Marketing catfish (Clarias Sp) City Balfour Ulu Ogan Ogan. This research was conducted in the City of Balfour OKU District. Determination lokasis done intentionally (purposive) on the basis that the business catfish (Clarias Sp) majority cultivated in Kota Balfour Ulu Ogan Ogan. Implementation of field research conducted in February-July 2015. The research method used in this research is the survey method used to obtain facts on the ground by using a questionnaire as a data collection tool of catfish farmers in Kota Balfour Ulu Ogan Ogan. The sampling method used was stratified random method lopsided (Dispropotionated stratified random sampling). Where from a total of 17 catfish farmers who do cattle catfish farmers have taken 10 samples of catfish homogeneous with an average over an area of ​​2 x 6 m2 and 3 x 6 m2. The results showed that (1) Based on the results of calculations that revenue catfish farmers in Kota Balfour Ulu Ogan Ogan has an average of Rp. 23,442,356.66, - per year (2) Based on the survey results revealed that the profit on the cost of production of 3.72 catfish farmers so we can say that the business profitable catfish and marketing of the highest margin obtained retailers on the second channel that fish farmers catfish sell their products to wholesalers, then sell to pengumupul, then sold to retailers and sold to the final consumer.